Pengaruh Likuiditas, Solvabilitas, dan Aktivitas Terhadap Profitabilitas Perusahaan Tekstil dan Garmen yang Terdaftar di BEI - Rumantas, Ivan (Jurnal Riset Akuntansi Politala, 2024)
The purpose of this research is to examine the impact of Liquidity, Solvability, and Activity on the Profitability of Textile and Garment companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. This research is a quantitative study using purposive sampling method. The study examines 100 data points from textile and garment sector companies listed on the IDX for the period 2018 - 2022 using the Statistical Package for Social Science (SPSS). Multiple linear regression analysis is used as the data analysis method. The results of this research indicate that Liquidity, Solvability, and Activity simultaneously influence Profitability. Liquidity partially does not have a significant effect on Profitability. Solvability partially does not significantly affect Profitability. Activity partially has a positive but not significant effect on Profitability. The limitation of this research is that the researcher only investigates companies in the textile and garment sector. Further research can hopefully be conducted in other sectors such as the pharmaceutical sector. This research is expected to increase insights, especially in company management, as a basis for decision-making to improve company profitability.